Translation Editology: Conceptualising the Unknown Known Interdisciplinary Area of Translation Studies - Odrekhivska, Iryna (Respectus Philologicus, 2017)
The present article is an attempt to examine the status, present the legitimacy and underscore the complexity of the field of ‘translation editology’ within a broad interdisciplinary framework of Translation Studies. This area of translation research is focused on the theoretical and critical reflection on the editorial and publishing practice of translated literature. The overriding objective of the paper is to elaborate an interpretative mechanism of editorial practices in translation and to portray its practical application. Following this line, a three-layer model of translation editorial analysis is suggested. While at the micro-level the functional structural analysis elicits how the text is mediated through specific instances of language use, the meso-level relates to interpersonal dimension centring on translator’s relation to the authorial intentions and the way of their actualisation and concretisation. The macro-level of analysis is discursive, reviews the editor’s “tendentious rewriting” or manipulation of the target text. This model is probed in the analysis of 1983 editorial work performed by Victor Koptilov for the re-publication of 1912 Ukrainian translation of Longfellow’s masterpiece The Song of Hiawatha.